Snake Venom Proteomics of Samar Cobra (Naja samarensis) from the Southern Philippines: Short Alpha-Neurotoxins as the Dominant Lethal Component Weakly Cross-Neutralized by the Philippine Cobra Antivenom - Palasuberniam, Praneetha; Chan, Yi Wei; Tan, Kae Yi; Tan, Choo Hock (Frontiers in Pharmacology, 2021)
The Samar Cobra, Naja samarensis, is endemic to the southern Philippines and is a WHO-listed Category 1 venomous snake species of medical importance. Envenomation caused by N. samarensis results in neurotoxicity, while there is no species-specific antivenom available for its treatment. The composition and neutralization of N. samarensis venom remain largely unknown to date. This study thus aimed to investigate the venom proteome of N. samarensis for a comprehensive profiling of the venom composition, and to examine the immunorecognition as well as neutralization of its toxins by a hetero-specific antivenom. Applying C18 reverse-phase high-performance liquid chromatography (RP-HPLC) and tandem mass spectrometry (LC-MS/MS), three-finger toxins (3FTx) were shown to dominate the venom proteome by 90.48% of total venom proteins. Other proteins in the venom comprised snake venom metalloproteinases, phospholipases A2, cysteine-rich secretory proteins, venom nerve growth factors, L-amino acid oxidases and vespryn, which were present at much lower abundances. Among all, short-chain alpha-neurotoxins (SαNTX) were the most highly expressed toxin within 3FTx family, constituting 65.87% of the total venom proteins. The SαNTX is the sole neurotoxic component of the venom and has an intravenous median lethal dose (LD50) of 0.18 µg/g in mice. The high abundance and low LD50 support the potent lethal activity of N. samarensis venom. The hetero-specific antivenom, Philippine Cobra Antivenom (PCAV, raised against Naja philippinensis) were immunoreactive toward the venom and its protein fractions, including the principal SαNTX. In efficacy study, PCAV was able to cross-neutralize the lethality of SαNTX albeit the effect was weak with a low potency of 0.20 mg/ml (defined as the amount of toxin completely neutralized per milliliter of the antivenom). With a volume of 5 ml, each vial of PCAV may cross-neutralize approximately 1 mg of the toxin in vivo. The findings support the potential para-specific use of PCAV in treating envenomation caused by N. samarensis while underscoring the need to improve the potency of its neutralization activity, especially against the highly lethal alpha-neurotoxins.